Proximal-type epithelioid sarcoma of the perineum: A case report and literature review - Xia, Shijun; Wu, Wenjiang; Ma, Lijuan (Frontiers in Oncology, 2023)
Proximal-type epithelioid sarcoma of the perineum is a rare soft-tissue malignancy, and only 55 cases have been reported in the English literature to date. This tumor has an indetectable early symptom and frequent recurrences. Here, we present the case of a 31-year-old man with proximal-type epithelioid sarcoma of the perineum who underwent wide excision. Further, we reviewed the current literature regarding differential diagnosis and management of this disease.